Autism as Rhetoric: Exploring Watershed Rhetorical Moments in Applied Behavior Analysis Discourse - Alicia A. Broderick (Disability Studies Quarterly, 2011)
This manuscript offers an analysis of what I argue are three watershed moments in contemporary autism and applied behavior analysis (ABA) rhetoric (1987-2010). The first of these moments is the 1987 publication of O. I. Lovaas's treatment effect study, which introduced the rhetoric of recovery from autism and linked this rhetorical construct with a particular intervention methodology—ABA. The second moment consists in the 1993 publication of Catherine Maurice’s autobiographical account of employing Lovaas-style ABA intervention programs with her two young children—an account that both popularizes Lovaas's rhetorical construct of recovery and reiterates its linking with ABA, but more significantly, that also introduces to popular autism discourse the rhetoric of science as a means of constituting the legitimacy of ABA. The third watershed moment in contemporary autism rhetoric is the 2005 establishment of the organization Autism Speaks, which has effectively changed the face of autism rhetoric through its comprehensive deployment of corporate-style rhetorical and political strategy.
Keywords: Applied behavior analysis; autism; Autism Speaks; parenting; recovery; rhetoric